PENGEMBANGAN MODEL E-CAREER UNTUK MENINGKATKAN KEPUTUSAN KARIR SISWA SMA NEGERI 3 MAKASSAR - fadillah fasha; Abdullah Sinring; Farida Aryani (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
This study aims: (1) To develop career information service model based on electronic media (e-career) which acceptable in improving students’ career decision at SMAN 3 Makassar. (2) To know the effectivity of career information service model based on electronic media (e-career) in improving students’ career decision at SMAN 3 Makassar. The study was a research and development which referred to the research stages by Borg and Gall. The research data were collected by employing interviews, questionnaires, and scales of measurement, as well as the Focus Group Discussion (FGD) techniques. The results of the study revealed that (1) the development of the acceptable electronic-based media (e-career) of career information services model in improving students’ career decisions obtained high rating scale from the experts and a very good response from the counseling teachers and students, where it was acceptable and feasible to be used in SMAN 3 Makassar; (2) The application of electronic-based media (e-career) of career information services model was effective in improving students career decision at SMAN 3 Makassar.